Slavic Reference Works and the Representation of Slovene: A Case Study - Šipka, Danko; Browne, Wayles (Slovenski jezik / Slovene Linguistic Studies, 2024)
The present paper uses the example of the Cambridge Handbook of Slavic Linguistics to elucidate the process of documenting Slavic languages in reference works: the rationale for the project and its contextualization amid other reference works for Slavic languages; the execution of the project, from the selection of the topics and authors to providing editors’ feedback to refereeing the submissions using external reviewers, and the content of the volume. Special attention is devoted to how the Slovene language is represented in this volume.